Clinical Significance of Glycated Hemoglobin (HbA1c) - Haque, K M H S Sirajul; Siddiqui, Mahmudur Rahman (Anwer Khan Modern Medical College Journal, 2013)
Not available DOI: http://dx.doi.org/10.3329/akmmcj.v4i1.13676 AKMMC J 2013; 4(1): 3-5